2014
DOI: 10.7314/apjcp.2014.15.3.1241
|View full text |Cite
|
Sign up to set email alerts
|

Cinobufacin Suppresses Cell Proliferation via miR-494 in BGC-823 Gastric Cancer Cells

Abstract: Cinobufacin is used clinically to treat patients with many solid malignant tumors. However, the mechanisms underlying action remain to be detailed. Our study focused on miRNAs involved in cinobufacin inhibition of GC cell proliferation. miRNA microarray analysis and real time PCR identified miR-494 as a significant cinobufacinassociated miRNA. In vivo, ectopic expression of miR-494 inhibited the proliferation and induced apoptosis of BGC-823 cells on CCK-8 and flow cytometry analysis. Further study verified BA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 24 publications
2
20
0
Order By: Relevance
“…The reaction was run in 20 ml that included 50 ng of cDNA and 0.3 nM of the corresponding primers. The U6 and mir-494 primers sequences were obtained from Zhou et al 30 For U6 forward primer sequence was ATTGGAACGA-TACAGAGAAGATT and the reverse was GGAACGCTTCAC-GAATTTG. For mir-494, the forward primer sequence was TGACCTGAAACATACACGGGA while the reverse was TATCGTTGTACTCCACTCCTTGAC.…”
Section: Rt-pcrmentioning
confidence: 99%
“…The reaction was run in 20 ml that included 50 ng of cDNA and 0.3 nM of the corresponding primers. The U6 and mir-494 primers sequences were obtained from Zhou et al 30 For U6 forward primer sequence was ATTGGAACGA-TACAGAGAAGATT and the reverse was GGAACGCTTCAC-GAATTTG. For mir-494, the forward primer sequence was TGACCTGAAACATACACGGGA while the reverse was TATCGTTGTACTCCACTCCTTGAC.…”
Section: Rt-pcrmentioning
confidence: 99%
“…In addition, miR-143 expression was identified to be significantly decreased in cervical cancer, and associated with tumor size, positive lymph node metastasis and HPV16 infection (10). A previous study demonstrated that the expression level of miR-145 was significantly decreased in human cervical cancer miR-494 inhibits cervical cancer cell proliferation through upregulation of SOCS6 expression LEI CHENG 1,2 , BEIHUA KONG 1 , YING ZHAO 2 and JIE JIANG tissues when compared with corresponding adjacent normal tissues and associated with tumor progression, and poor prognosis (11). Furthermore, miR-494 serves as a tumor suppressor miRNA and abnormal expression of miR-494 has been identified in a number of tumor tissue types (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…So far it is the fourth most frequently diagnosed cancer as each year more than one million patients are annually diagnosed with gastric cancer (Ferlay et al, 2010;Hernandez et al, 2010;Basiri et al, 2014;Behnampour et al, 2014;Calik et al, 2014;Deng et al, 2014;Khoshbaten et al, 2014;Karim et al, 2014;Lu et al, 2014;Unal et al, 2014;Yang et al, 2014;Zhou et al, 2014). The incidence of stomach cancer varies geographically, with a much higher prevalence in Eastern countries than in the Western ones .…”
Section: Introductionmentioning
confidence: 99%